ETNOMATEMATIKA PADA KERAJINAN ANYAMAN TIKAR PANDAN - Mauliyana, Hely; Rustam, Rustam; Sayu, Silvia (Jurnal AlphaEuclidEdu, 2023)
Mathematics lessons are considered abstract lessons far from everyday life. Therefore, the task of mathematics teachers is to present mathematical concepts in students' lives to mathematics learning. Ethnomathematics is an approach that links mathematics and culture. The method used is to explore the concept of ethnomathematics, one of which is in the craft of woven pandan mats as a student learning resource. The aim of this research is to describe the mathematical concepts contained in woven pandan mats in the Padang Tikar community and to use them as a mathematics learning resource in the form of LKPD. The form of research used in this research is exploratory research with an ethnographic approach. The subjects in this research were pandan mat craftsmen. The instruments used were observation guidelines and interview sheets. The data analysis technique used in this research is the Miles and Huberman model of data analysis. The results of the research show that there are several activities of woven pandan mat craftsmen, namely: determining which pandan is suitable for use, determining the length of the pandan, cleaning and determining the width of the ilik, boiling the ilik, soaking the ilik, drying the ilik, dyeing the ilik, making woven motifs, and determining the length and width pandan mat. The mathematical concepts contained are: sets, logic, comparison, multiples, fold symmetry, geometry, multiplication of integers, and measurement. From the mathematical concepts obtained, it will be used as a LKPD, namely geometry where the material taken is squares and rectangles.